Choose the product.
-7p3(4p2 + 3p - 1)

Question

Asked 1/16/2015 11:06:42 AM

Updated 1/16/2015 7:16:22 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by janezeshun [1/16/2015 7:15:05 PM]

s

eturker|Points 3077|

Question

Asked 1/16/2015 11:06:42 AM

Updated 1/16/2015 7:16:22 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by janezeshun [1/16/2015 7:15:05 PM]

Rating

3

-7p^3(4p^2 + 3p - 1)

= -7p^3*4p^2 - 7p^3*3p + 7p3

= -28p^5 - 21p^4 + 7p^3

= -7p^3*4p^2 - 7p^3*3p + 7p3

= -28p^5 - 21p^4 + 7p^3

Added 1/16/2015 7:16:22 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [1/17/2015 10:39:50 AM]

(n + 8)(n - 2)

Question

Updated 1/16/2015 11:23:52 AM

1 Answer/Comment

(n + 8)(n - 2)

= n^2 - 2n + 8n - 16;

= n^2 + 6n - 16

= n^2 - 2n + 8n - 16;

= n^2 + 6n - 16

Added 1/16/2015 11:23:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [1/16/2015 11:32:00 AM]

x3y3 **Weegy:** Please be more specific with your question. **User:** Simplify -3p3 + 5p + (-2p2) + (-4) - 12p + 5 - (-8p3) **Weegy:** Please state your questions.
**User:** 5m + 2n, n - 3m, and 7 - 3n (More)

Question

Updated 1/15/2015 6:02:40 PM

2 Answers/Comments

-3p^3 + 5p + (-2p^2) + (-4) - 12p + 5 - (-8p^3)

= -3p^3 + 8p^3 + 5p - 12p - 2p^2 - 4 + 5

= 5p^3 - 2p^2 - 7p + 1

= -3p^3 + 8p^3 + 5p - 12p - 2p^2 - 4 + 5

= 5p^3 - 2p^2 - 7p + 1

Added 1/15/2015 6:01:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [1/16/2015 11:42:25 AM]

5m + 2n + (n - 3m) + (7 - 3n)

= 5m + 2n + n - 3m + 7 - 3n

= 2m + 7

= 5m + 2n + n - 3m + 7 - 3n

= 2m + 7

Added 1/15/2015 6:02:40 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [1/16/2015 11:44:20 AM]

2ay2 + 5ay - 3a **Weegy:** 2ay^2 + 5ay - 3a
= a(2y^2 + 5y - 3)
= a(2y - 1)(y + 3) (More)

Question

Expert Answered

Updated 1/16/2015 10:19:30 AM

0 Answers/Comments

Select the correct difference.
-3z7 - (-5z7)
User: Select the correct difference.
5d2 + 4d - 3 less 2d2 - 3d + 4
**Weegy:** (5d^2 + 4d - 3) - (2d^2 - 3d + 4) = 3d^2 + 7d - 7 **User:** Simplify m - {n + [p - (m + n - p)]}. **Weegy:** m - {n - [p + (m + n - p)]} = m - [n - (p + m + n - p)] = m - [n - (m + n)] = m - (n - m - n) = m - (-m) = m + m = 2m (More)

Question

Updated 1/16/2015 5:29:42 PM

1 Answer/Comment

-3z^7 - (-5z^7)

= -3z^7 + 5z^7

= 2z^7

= -3z^7 + 5z^7

= 2z^7

Added 1/16/2015 5:18:47 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [1/16/2015 5:29:50 PM]

Factor -2bk2 + 6bk - 2b. **Weegy:** -2bk^2 + 6bk - 2b = -2b(k^2 - 3k + 1) (More)

Question

Updated 1/16/2015 12:10:20 PM

0 Answers/Comments

31,264,206

questions answered

denyang

$216.05

Hearts 5,228 Views 1,527,548 Streams 616

phpmicro

$196.90

Hearts 4,074 Views 936,013 Streams 315

maydj

$194.15

Hearts 4,226 Views 1,122,647 Streams 424

sampi1890

$163.15

Hearts 4,547 Views 1,790,483 Streams 573

emdjay23

$152.05

Hearts 3,472 Views 847,311 Streams 272

miyaka

$150.25

Hearts 3,651 Views 933,217 Streams 478

Flora1988

$141.95

Hearts 3,466 Views 612,698 Streams 294

Peachygguk97

$139.05

Hearts 3,083 Views 396,569 Streams 198

There are no comments.